2006
DOI: 10.1590/s1415-43662006000200032
|View full text |Cite
|
Sign up to set email alerts
|

Movimento do herbicida tebutiuron em dois solos representativos das áreas de recarga do aqüífero Guarani

Abstract: O movimento do herbicida tebutiuron foi analisado em um Latossolo Vermelho Distrófico psamítico (LVdq) e um Neossolo Quartzarênico Órtico típico (RQo), representativos das áreas de recarga do aqüífero Guarani no Brasil, tendo como fatores influenciadores, a condutividade hidráulica (K), o teor de carbono orgânico (CO) e o teor de argila (TAr). O presente estudo foi realizado em colunas de solos indeformados, com aplicação do produto comercial contendo o herbicida em discussão. Esses parâmetros evidenciam certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
0
8
0
5
Order By: Relevance
“…In recent studies, results on the herbicide contamination of aquifer waters are presented, and several authors highlight the necessity to monitor products in order to protect the water spring (Gomes et al, 2006;Queiroz et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, results on the herbicide contamination of aquifer waters are presented, and several authors highlight the necessity to monitor products in order to protect the water spring (Gomes et al, 2006;Queiroz et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, after a four-year monitoring study, Gomes et al (2006) found that the herbicide tebuthiuron was detected in semi-artesian wells with a depth of 53 m, in Ribeirão Preto, Brazil. These authors relate the fact to the use of this product in cane sugar and to the physical characteristics of the soil in the watershed that was assessed.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the more contact time of the herbicide with the straw, the less its transposition to the soil, regardless of the simulated rain quantity, reducing by about 30% the total leached product when this remained exposed for 28 days after application. The active principle of this herbicide (tebuthiuron) presents long half-life, about a year in soils with high carbon content and little rain (Chang and Strizke, 1977;Helling, 2005;Gomes et al, 2006); it may have its half-life reduced up to 20 days under specific soil conditions (moisture, organic matter concentration, microbial community) and climate (temperature, radiation) (Cerdeira et al, 2007). In this study, tebuthiuron was not effective in controlling after 45 days without rain, indicating that the product may have been volatilized and/or photodegraded during this period.…”
Section: Resultsmentioning
confidence: 99%
“…O herbicida tebuthiuron, de forma similar ao s-metolachlor, também apresenta caráter não-iônico, degradação principal por via microbiana, sorção correlacionada com os teores de matéria orgânica, argila e com a CTC do solo (Gomes et al, 2006;Matallo et al, 2005;Rodrigues & Almeida, 2005). Estudos têm demonstrado que ambos os produtos têm mobilidade reduzida no perfil dos solos, o que contribui para o adequado controle das plantas daninhas devido à permanência de mais moléculas na camada superficial e menor potencial de contaminação ambiental (Souza et al, 2008;Gomes et al, 2006;Procópio et al, 2001).…”
Section: Resultsunclassified
“…Estudos têm demonstrado que ambos os produtos têm mobilidade reduzida no perfil dos solos, o que contribui para o adequado controle das plantas daninhas devido à permanência de mais moléculas na camada superficial e menor potencial de contaminação ambiental (Souza et al, 2008;Gomes et al, 2006;Procópio et al, 2001).…”
Section: Resultsunclassified